A multi-layered combination structure solar photothermal film
By using a multi-layered solar thermal film structure, the problems of high reflectivity under oblique sunlight incidence and aging at high temperatures are solved, improving light energy utilization efficiency and heat conduction efficiency, expanding the applicable temperature range, and extending service life.
Patent Information
- Application Number
- CN202311478441.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-11-08
AI Technical Summary
Existing solar thermal films have high reflectivity under oblique sunlight conditions, resulting in low light energy utilization efficiency. They are also prone to aging at high temperatures, leading to a decrease in photothermal conversion efficiency and low heat conduction efficiency, making it difficult to meet the requirements for efficient and stable operation.
The solar thermal film employs a multi-layered composite structure, including a large-angle broadband anti-reflection film stack, a high-efficiency light-absorbing film stack, and a high-efficiency thermally conductive film stack, which are combined from top to bottom. High-efficiency materials such as graphene films and graphite-like carbon-based films are used to optimize the film structure to improve light energy utilization and heat conduction efficiency, and enhance stability.
It achieves higher solar energy utilization efficiency, more efficient heat conduction, a wider operating temperature range, and lower light attenuation, extending its service life and enabling stable operation in different temperature scenarios.
Smart Images

Figure CN117490259B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a multi-layered composite structure solar thermal thin film, belonging to the field of solar thermal new energy functional thin film technology. Background Technology
[0002] The development and utilization of renewable energy, represented by solar energy, is a key approach and direction for human society to promote energy structure transformation and solve environmental problems. The efficient capture of solar radiation energy using specific devices and its conversion into other safe and clean energy forms such as heat, electricity, and chemical energy is a key focus of new energy research and development. Four basic technological pathways have been established and commercially applied: solar thermal utilization, solar photovoltaic power generation, solar photochemical utilization, and solar photobiological utilization. Among these, solar thermal utilization technology, depending on the operating temperature, has formed various scenarios for low-temperature, medium-temperature, and high-temperature utilization. It has been widely used in solar water heaters, dryers, industrial hot water and steam, hot air or heat transfer oil systems, solar air conditioning or heating systems, solar metallurgy, and large-scale solar thermal power plants. Compared with other solar energy utilization pathways, it has significant characteristics of being green, low-carbon, environmentally friendly, highly efficient, safe, clean, and capable of long-term storage and utilization, and will become an important component of the future new energy structure.
[0003] Solar thermal utilization involves multiple stages, including solar concentrating, heat collection, heat exchange, heat storage, and a heat-work conversion cycle system. Among these, the efficiency and stability of collecting sunlight and converting light energy into heat energy during the solar concentrating and heat collection process determine the overall quality and energy efficiency of the solar thermal utilization system. To this end, various photothermal conversion devices have been researched and developed to meet the needs of solar thermal utilization technology. The main technical approach uses solar spectral selective absorption coatings, and the energy efficiency is evaluated using the a / e coefficient, where a represents the solar absorptivity and e represents the thermal emissivity. An ideal spectral selective photothermal film requires the highest possible absorptivity (a > 98%) in the main wavelength band of the solar spectrum (<3μm) to ensure maximum photothermal conversion efficiency; and the lowest possible thermal emissivity (e < 5%) in the thermal radiation band (>3μm) to minimize heat loss due to external thermal radiation during heating and high-temperature operation; simultaneously, it must maintain structural and performance stability in hot air (100-900℃) atmospheres. Therefore, in order to improve the energy efficiency of photothermal films, thin film coating technology that optimizes the light absorption and radiation ratio is constantly being improved and enhanced. From materials to film structure and preparation technology, great progress has been made, and many new achievements have been commercialized and promoted.
[0004] Existing technologies have evolved from early applications of black heat-absorbing thin films coated on metal substrates. However, these films suffer energy losses of up to 45% due to the long-wavelength radiation emitted after heat absorption and temperature rise, resulting in a solar thermal utilization efficiency of less than 50%. In recent years, research and development of spectrally selective thin film materials and structures have significantly improved the efficiency of solar thermal films. In terms of heat-absorbing materials, development has focused on intrinsically absorbing materials such as borosilicates, W, Mo, Cr, or carbides and nitrides of some transition metals, ZrB2, HfC, and TiAlN. The transformation of film structures from single-layer to double-layer to multi-layer structures is also significant. Representative examples include substrate / TiAlN / SiO2 double-layer thin film structures, semiconductor / metal multilayer structures, metal-dielectric material multilayer structures, and selectively transparent film-light-absorbing material multilayer structures. These advancements have enabled solar thermal films to achieve a heat collection efficiency of 89% and reduce thermal emissivity to 10%.
[0005] However, existing technologies still have prominent problems such as high solar spectral reflectivity under oblique sunlight conditions leading to low light energy utilization efficiency, easy aging under high temperature for long-term operation leading to a decrease in photothermal conversion efficiency, and low heat conduction efficiency. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention proposes a solar thermal thin film with a multi-layered composite structure.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A multi-layered solar thermal film is composed of a large-angle broadband anti-reflection film stack 001, a high-efficiency light-absorbing film stack 002, and a high-efficiency thermally conductive film stack 003 arranged sequentially from top to bottom on the substrate surface. The stack 001 is a broadband antireflection layer composed of one or more dielectric materials selected from SiO2, Si3N4, TiO2, Al2O3, Nb2O5, Ta2O5, ZrO2, and MgF2, with a thickness controlled within 3 μm. The stacked layer 002 is a light-absorbing layer composed of one or more of Si, Ge, W, Mo, Ni, Cu, Ag, Cr, V, Ti, Zr, La, Nb, Ta, Al or their oxides, borides, and nitrides, with a thickness controlled within 3 μm; The stack 003 is a thermally conductive layer in which one or more of the following materials are bonded to the substrate: graphene film (GPE), diamond-like carbon film (DLC), graphite-like carbon film (GLC), polymer-like carbon film (PLC), and AlN film, with a thickness controlled within 3 μm.
[0008] Furthermore, the stack 001 is composed of SiO2, TiO2, and Si3N4, the stack 002 is composed of Si, TiB2, and Mo-Al2O3, and the stack 003 is composed of AlN and graphite-like carbon film (GLC).
[0009] Furthermore, the multi-layered composite structure on the substrate consists of, from top to bottom, 120nm SiO2 / 70nm TiO2 / 90nm Si3N4 / 300nm Si / 50nm TiB2 / 150nm Mo-Al2O3 / 10nm AlN / 100nm GLC / substrate.
[0010] Furthermore, the stack 001 is composed of SiO2 and TiO2, the stack 002 is composed of Si, TiB2 and Mo-Al2O3, and the stack 003 is composed of a graphite-like carbon film (GLC).
[0011] Furthermore, the multi-layered composite structure on the substrate consists of, from top to bottom, 130nm SiO2 / 60nm TiO2 / 300nm Si / 50nm TiB2 / 200nm Mo-Al2O3 / 200nm GLC / substrate.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. A multi-layered solar thermal film, comprising, from top to bottom, a large-angle broadband antireflective film stack 001, a high-efficiency light-absorbing film stack 002, and a high-efficiency thermally conductive film stack 003 on the substrate surface. The stacks 001, 002, and 003 are combined into a single integrated structural design. Its novelty and innovation are reflected in: higher solar energy utilization efficiency, higher heat conduction efficiency, a wider operating temperature range, lower light attenuation coefficient, and longer service life.
[0013] 2. Higher sunlight utilization efficiency is achieved through a design method in this invention that treats all the combined film layers as an equivalent admittance. By controlling the stacked 001, a wide-angle broadband anti-reflection effect on the sunlight spectrum is achieved. This ensures that the average reflectance of sunlight from the visible to the infrared spectrum (<3μm) is less than 1.5% under ±60° oblique incidence conditions, allowing more light energy to enter the light absorption layer and improving the photothermal conversion efficiency. In contrast, existing anti-reflection layer designs can only meet the requirements of normal or small-angle oblique incidence and mainly have a good narrow-band anti-reflection effect on the visible spectrum. However, sunlight is obliquely incident on the surface of the heat collection film for most of the time. Existing products have a reflectance of more than 10% from the visible to the infrared spectrum under 60° oblique incidence conditions, which affects the improvement of light energy utilization efficiency.
[0014] 3. The higher thermal conductivity is achieved by combining the stacked 003 film with the substrate to form a high-efficiency thermal conductivity layer. Existing technologies generally use oxides, carbides, nitrides, etc., of high-temperature resistant metals or alloys or semiconductors to form the bonding layer between the light absorber and the substrate. These materials have low thermal conductivity; for example, Ag and Cu, which have the highest thermal conductivity among metals, have thermal conductivity of 420 (W / m·K) and 401 (W / m·K), respectively, while other metals, alloys, and dielectric ceramic materials have even lower thermal conductivity. The high-efficiency thermal conductivity thin film materials used in this invention, such as graphene film (GPE) and graphite-like carbon film (GLC), have thermal conductivity of 5300 (W / m·K) and 2200 (W / m·K), respectively. Through innovation in materials and film structure, the thermal conductivity of the photothermal film is greatly improved, while also effectively reducing thermal radiation.
[0015] 4. A wider operating temperature range, lower light attenuation coefficient, and longer service life are achieved through the design and use of film materials in this invention. These materials have been verified to have excellent resistance to strong light impact, thermal shock, temperature and humidity fluctuations, and acid / alkali / salt spray and sulfide contamination. They exhibit good stability and resistance to environmental aging, making them suitable for various high, medium, and low temperature environments below 900℃. The robust combination of the broadband antireflective layer 001, the light-absorbing material layer 002, the high-efficiency thermally conductive layer 003, and the substrate forms an effective overall self-protective structure for the film system. Compared to existing technologies, this structure maintains structural and performance stability better in hot air (100-900℃) atmospheres.
[0016] 5. The solar thermal thin film with the multi-layer composite structure designed according to the present invention can be manufactured on an industrial scale using mature physical vapor deposition (PVD) or chemical vapor deposition (CVD) methods, preferably using multi-cavity continuous magnetron sputtering coating equipment. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the solar thermal thin film structure of the multi-layered composite structure of the present invention; Figure 2 This is a schematic diagram of the multi-layer composite film structure of Embodiment 1 of the present invention; Figure 3 This is a schematic diagram of the light absorptivity and thermal emissivity spectral curves of Embodiment 1 of the present invention. Detailed Implementation
[0018] The technical solution and effects of the present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0019] This invention discloses a multi-layered composite structure of solar thermal thin film, such as... Figure 1As shown, the substrate surface is composed of a large-angle broadband antireflective film stack 001, a high-efficiency light-absorbing film stack 002, and a high-efficiency thermally conductive film stack 003, arranged sequentially from top to bottom.
[0020] When designing, developing and preparing solar thermal films using the structure described in this invention, in accordance with the principles of high energy efficiency, long lifespan and good economy, several film system structures with different materials and film thicknesses can be formed according to the requirements of the application scenario and the preparation process conditions.
[0021] First, the film material and structure of the stack 003 bonded to the substrate are selected: based on the matching of thermal conductivity of the substrate material, operating temperature, and different light absorption stacks, one or more materials are selected from graphene film (GPE), diamond-like carbon film (DLC), graphite-like carbon film (GLC), polymer-like carbon film (PLC), and AlN film to bond with the substrate to form a high-efficiency thermal conductivity layer. For example, graphite-like carbon film (GLC) can be selected as the high-efficiency thermal conductivity layer, or a combination of graphite-like carbon film (GLC) and AlN film can be selected, or a combination of graphite-like carbon film (GLC), polymer-like carbon film (PLC), and AlN film can be selected to form a high-efficiency thermal conductivity layer, and so on.
[0022] The aforementioned films can be obtained using well-known and mature technologies or preparation methods. Graphene films (GPE) and polymer-like carbon films (PLC) are prepared using CVD or PECVD deposition techniques in a vacuum containing carbon gases such as methane; diamond-like carbon films (DLC) are prepared using SP... 3 The phase content is 50%-85%, and the preferred preparation technology is graphite target vacuum cathode arc discharge electromagnetic confinement filtration deposition. The preferred preparation technology is graphite target vacuum plasma magnetron sputtering for graphite-like carbon thin films (GLC), and the preferred preparation technology is Al target vacuum nitrogen-filled magnetron sputtering for AlN thin films.
[0023] Secondly, based on the determined film material and structure of the stacked layer 003, the film material and structure of the stacked layer 002 are matched. One or more of Si, Ge, W, Mo, Ni, Cu, Ag, Cr, V, Ti, Zr, La, Nb, Ta, Al or their oxides, borides, and nitrides are selected to form the light-absorbing stacked layer 002, achieving efficient absorption of solar energy within 3μm and forming the lowest thermal emissivity with the underlying thermally conductive layer. For example, the stacked layer 003 can be selected as a single film layer to form a "substrate / GLC" structure or as a double film layer to form a "substrate / GLC / AlN" structure, and the stacked layer 002 can be selected as a three-layer structure of Mo-Al2O3 / TiB2 / Si to form the best match.
[0024] Finally, based on the determination of the film materials and structures of stack 003 and stack 002, stack 001 is matched, and one or more dielectric materials such as SiO2, Si3N4, TiO2, Al2O3, Nb2O5, Ta2O5, ZrO2, and MgF2 are selected to form a broadband antireflection film with large-angle incident light, together with the determined film structures of stack 003 and stack 002. The design method can use the equivalent admittance method and simulation calculation of film system design software to achieve the optimal result, and finally determine the film thickness of each layer. For example, after the stacked layers 003 and 002 have been determined to be a substrate / GLC / AlN / Mo-Al2O3 / TiB2 / Si structure, Si3N4 / TiO2 / SiO2 is selected as the wide-angle incident broadband antireflection film structure, and the resulting multi-layered solar thermal film structure is: substrate / GLC / AlN / Mo-Al2O3 / TiB2 / Si / Si3N4 / TiO2 / SiO2; for example, after determining the substrate / GLC / Mo-Al2O3 / TiB2 / Si structure, TiO2 / SiO2 is selected as the wide-angle incident broadband antireflection film structure, and the resulting multi-layered solar thermal film structure is: substrate / GLC / Mo-Al2O3 / TiB2 / Si / TiO2 / SiO2.
[0025] The following embodiments were constructed by implementing the above method and through simulation design and optimization using thin film design software. Example 1
[0026] like Figure 2 As shown, the film structure in this embodiment is specifically as follows: substrate / 100nm GLC / 10nm AlN / 150nm Mo-Al2O3 / 50nm TiB2 / 300nm Si / 90nm Si3N4 / 70nm TiO2 / 120nm SiO2.
[0027] The multi-layered photothermal film exhibits an average surface reflectivity of approximately 1.5% in the wavelength range below 3 μm, a light absorption rate of 98%, and a thermal emissivity of approximately 5%. Figure 3 The membrane structure is stable and has strong anti-aging properties. It has been tested and can work stably at temperatures below 900℃.
[0028] The above embodiments are preferably manufactured using a multi-cavity continuous magnetron sputtering coating equipment. The specific process is as follows: the cleaned substrate is sent into the coating chamber, and graphite-like, AlN, doped Mo-Al2O3, TiB2, Si, Si3N4, TiO2 and SiO2 of specific thicknesses are sputtered sequentially in the chamber loaded with different target materials to complete the preparation of a multi-layered combined photothermal thin film. Example 2
[0029] Unlike Example 1, the film structure in this example is specifically composed of: substrate / 200nm GLC / 200nm Mo-Al2O3 / 50nm TiB2 / 300nm Si / 60nm TiO2 / 130nm SiO2.
[0030] The photothermal film with this multi-layered structure has an average surface reflectivity of about 1.7% in the wavelength band below 3μm, a light absorption rate of 98%, and a thermal emissivity of about 5%. The film structure is stable and has strong anti-aging properties. It has been tested and can work stably at temperatures below 900℃.
[0031] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A solar thermal thin film with a multi-layered composite structure, characterized in that, The solar thermal film is composed of a large-angle broadband anti-reflection film stack 001, a high-efficiency light absorption film stack 002, and a high-efficiency thermal conductivity film stack 003, arranged from top to bottom on the substrate surface. The stack 001 is a broadband antireflection layer composed of one or more dielectric materials selected from SiO2, Si3N4, TiO2, Al2O3, Nb2O5, Ta2O5, ZrO2, and MgF2, with a thickness controlled within 3 μm. The stacked layer 002 is a light-absorbing layer composed of one or more of Si, Ge, W, Mo, Ni, Cu, Ag, Cr, V, Ti, Zr, La, Nb, Ta, Al or their oxides, borides, and nitrides, with a thickness controlled within 3 μm; The stack 003 is a thermally conductive layer in which one or more of the following materials are bonded to the substrate: graphene film, diamond-like carbon film, graphite-like carbon film, polymer-like carbon film, and AlN film, with a thickness controlled within 3 μm.
2. The solar thermal thin film with a multi-layered composite structure according to claim 1, characterized in that, The stack 001 is composed of SiO2, TiO2, and Si3N4, the stack 002 is composed of Si, TiB2, and Mo-Al2O3, and the stack 003 is composed of AlN and a graphite-like carbon-based thin film.
3. The solar thermal thin film with a multi-layered composite structure according to claim 2, characterized in that, The multi-layered composite structure of this solar thermal film on the substrate consists of, from top to bottom, 120nm SiO2 / 70nm TiO2 / 90nm Si3N4 / 300nm Si / 50nm TiB2 / 150nm Mo-Al2O3 / 10nm AlN / 100nm graphite-like carbon-based film / substrate.
4. The solar thermal thin film with a multi-layered composite structure according to claim 1, characterized in that, The stack 001 is composed of SiO2 and TiO2, the stack 002 is composed of Si, TiB2 and Mo-Al2O3, and the stack 003 is composed of a graphite-like carbon-based thin film.
5. The solar thermal thin film with a multi-layered composite structure according to claim 4, characterized in that, The multi-layered composite structure of this solar thermal film on the substrate consists of, from top to bottom, 130nm SiO2 / 60nm TiO2 / 300nm Si / 50nm TiB2 / 200nm Mo-Al2O3 / 200nm graphite-like carbon-based film / substrate.
Citation Information
Patent Citations
Solar selective absorption film system and preparation method thereof
CN102582150A
Ti-alloy nitride selective-absorption film system and preparation method thereof
CN103383155A
